PENGARUH RASIO KEUANGAN TERHADAP NILAI PERUSAHAAN YANG TERGABUNG DALAM INDEKS KOMPAS100 - G. A. Sri Oktaryani; Awafiq Abdurrazak; Iwan Kusuma Negara (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The firm’s goal is to maximize the firm value or wealth for its shareholders. The purpose of this research is to examine the effects of profitability ratio, liquidity ratio, solvency ratio, and activity ratio on the firm value which are part of Kompas-100 index during period 2015 – 2019. Sample are selected by using purposive sampling method. The analysis technique used is multiple linear regression analysis. This study indicate that the profitability, liquidity and activity ratio have positive and significant effect on firm value. Meanwhile, the solvability has a negative and significant effect on firm’s value.Keywords:Profitability; liquidity; solvability; activity; firm value